Pressure ulcer prevention knowledge among Jordanian nurses: a cross- sectional study - Qaddumi, Jamal (BioMed Central, 2014)
BACKGROUND: Pressure ulcer remains a significant problem in the healthcare system. In addition to the suffering it causes patients, it bears a growing financial burden. Although pressure ulcer prevention and care have improved in recent years, pressure ulcer still exists and occurs in both hospital and community settings. In Jordan, there are a handful of studies on pressure ulcer. This study aims to explore levels of knowledge and knowledge sources about pressure ulcer prevention, as well as barriers to implementing pressure ulcer prevention guidelines among Jordanian nurses. METHODS: Using a cross-sectional study design and a self-administered questionnaire, data was collected from 194 baccalaureate and master’s level staff nurses working in eight Jordanian hospitals. From September to October of 2011, their knowledge levels about pressure ulcer prevention and the sources of this knowledge were assessed, along with the barriers which reduce successful pressure ulcer care and prevention. ANOVA and t-test analysis were used to test the differences in nurses’ knowledge according to participants’ characteristics. Means, standard deviation, and frequencies were used to describe nurses’ knowledge levels, knowledge sources, and barriers to pressure ulcer prevention. RESULTS: The majority (73%, n = 141) of nurses had inadequate knowledge about pressure ulcer prevention. The mean scores of the test for all participants was 10.84 out of 26 (SD = 2.3, range = 5–17), with the lowest score in themes related to PU etiology, preventive measures to reduce amount of pressure/shear, and risk assessment. In-service training was the second source of education on pressure ulcer, coming after university training. Shortage of staff and lack of time were the most frequently cited barriers to carrying out pressure ulcer risk assessment, documentation, and prevention. CONCLUSIONS: This study highlights concerns about Jordanian nurses’ knowledge of pressure ulcer prevention. The results of the current study showed inadequate knowledge among Jordanian nurses about pressure ulcer prevention based on National Pressure Ulcer Advisory Panel guidelines. Also, the low level of nurses’ pressure ulcer knowledge suggests poor dissemination of pressure ulcer knowledge in Jordan, a suggestion supported by the lack of relationship between years of experience and pressure ulcer knowledge.